2019
DOI: 10.3892/etm.2019.7942
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA CCEPR suppresses colorectal cancer progression

Abstract: Long non-coding RNAs (lncRNAs) serve important roles in colorectal cancer. The aim of the present study was to investigate the expression and role of cervical carcinoma expressed PCNA regulatory (CCEPR) lncRNA in colorectal cancer progression. The results demonstrated that CCEPR expression was significantly higher in colorectal cancer tissues when compared with paired adjacent normal tissues. In addition, CCEPR expression was significantly higher in patients with advanced colorectal cancer (stage III/IV) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Further, the results of the current study demonstrated that the knockdown of the lncRNA TERC significantly increased the proliferation, migration, and invasion of the HGC-27 and SNU-1 GC cell lines. Numerous previous studies have reported that PCNA, EMT, and MMP9 play important roles in the proliferation, migration, and invasion of cancer cells (38)(39)(40)(41)(42)(43). Notably, in the present study, the results demonstrated that the lncRNA TERC knockdown significantly upregulated the expression levels of the EMT-related marker, E-cadherin, and downregulated the expression levels of PCNA, MMP9, and N-cadherin in the HGC-27 and SNU-1 GC cell lines.…”
Section: Discussionsupporting
confidence: 60%
“…Further, the results of the current study demonstrated that the knockdown of the lncRNA TERC significantly increased the proliferation, migration, and invasion of the HGC-27 and SNU-1 GC cell lines. Numerous previous studies have reported that PCNA, EMT, and MMP9 play important roles in the proliferation, migration, and invasion of cancer cells (38)(39)(40)(41)(42)(43). Notably, in the present study, the results demonstrated that the lncRNA TERC knockdown significantly upregulated the expression levels of the EMT-related marker, E-cadherin, and downregulated the expression levels of PCNA, MMP9, and N-cadherin in the HGC-27 and SNU-1 GC cell lines.…”
Section: Discussionsupporting
confidence: 60%
“…More importantly, the present study found that blocking lncRNA LINC00355 expression arrested the proliferation, invasion and migration of colon cancer cells and promoted apoptosis. Likewise, a previous study has validated that inhibition of the lncRNA CCEPR impedes invasion, proliferation, migration and cell cycle progression in colon cancer cells [32] . Similarly, suppression of the lncRNA AWPPH expression could suppress cell proliferation in colon cancer [33] .…”
Section: Discussionmentioning
confidence: 73%
“…A recent investigation showed a meaningful correlation between the overexpression of LINC00963 and the upregulation of MMP-2 and MMP-9 , proliferation, migration, and invasion of CRC cells [ 147 ]. Duan et al, revealed that the inhibition of the CCEPR lncRNA reduced the expression levels of MMP-2 and MMP-9 , and prevented EMT in CRC cells [ 148 ]. Pan et al, realized that the expression level of MMP-2 protein was notably decreased when PCA3 was knocked out.…”
Section: Targeting Mmps In Crc Treatmentmentioning
confidence: 99%